Social Innovation through the Integrated Elderly Family Development Program in Pekanbaru City - Khairul Rahman; Fadhlunnisa Rizkiy Agusriana Yulzam; Dita Fisdian Adni (Journal Public Policy, 2026)
This study aims to evaluate the effectiveness of the Integrated Elderly Family Development Program (BKL) in Pekanbaru and to identify areas needing improvement to enhance the well-being of the elderly optimally. This research employs a qualitative method with data collection techniques, including interviews, observations, and documentation, and utilizes Nvivo 12 Plus for data analysis. The findings indicate that the social innovation within the BKL Program in Pekanbaru includes the integration of health services, social welfare, economic improvement, food security, and social support through PosyanduLansia and PUSAKA; the implementation of a comprehensive approach involving various activities in a single location; and cross-sector synergy to enhance coordination and effectiveness of services. However, key challenges include inadequate cross-sector coordination leading to a lack of synchronization in services, limitations in health services that may result in a deterioration of health among the elderly, and economic non-productivity exacerbating the economic burden on families and the community. Addressing these challenges requires better coordination mechanisms, improvements in access and quality of health services, and the integration of economic empowerment programs to support the independence of the elderly. This research contributes to the understanding how integrated social innovation can be applied to improve the well-being of older adults.